An extraordinary experience: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story recounts a remarkable event in a person's life that leads to profound self-discovery and spiritual awakening. It emphasizes the importance of being open to new experiences and recognizing the lessons that can emerge from them, ultimately fostering a deeper connection with faith and purpose.